1984
DOI: 10.1128/mcb.4.9.1900
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulation of simian virus 40 early-region transcription from different overlapping promoters.

Abstract: During simian virus 40 lytic infection there is a shift in initiation sites used to transcribe the early region, which encodes large T and small t antigens. Early in infection, transcription is initiated almost exclusively from sites that are downstream of the origin of DNA replication, whereas transcripts produced later are initiated mainly from sites on the upstream side. We have used mutant virus and specially constructed plasmid DNAs to investigate the factors regulating this transcriptional shift. In our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 35 publications
4
38
0
Order By: Relevance
“…These findings with double-ori recombinants are consistent with our ideas regarding the regulation of SV40 early-region transcription (6,12). In addition, the peculiar behavior of these recombinants provides some revelations regarding normal early-region expression.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings with double-ori recombinants are consistent with our ideas regarding the regulation of SV40 early-region transcription (6,12). In addition, the peculiar behavior of these recombinants provides some revelations regarding normal early-region expression.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that the 299-bp deletion in IVS2-6 and SVIV-6 inactivates both the downstream and the upstream promoters suggests that sequences within the 72-bp and GC-rich repeat regions are important for upRNA information. Since our earlier study (6) showed that the enhancer sequences are not required for upRNA synthesis, it seems likely that transcription from the upstream sites requires the GC-rich repeats. The recent findings of Baty et al (2) also indicate that the GC-rich repeat region is involved in upRNA formation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The early promoter is composed of at least three spatially distinct elements: (i) the TATA box; (ii) a G-C-rich region; and (iii) the enhancer element. The TATA box, which is contained within a 17-bp A-T-rich sequence, dictates the position of the major early initiation sites (at nucleotides [nt] 5230 to 5237, 21 to 28 bp downstream from the TATA box) used preferentially before viral DNA replication (3,8,17). The G-C-rich region contains six copies of the sequence 5'-PyPyCCGCCC-3' in two direct repeat sequences of 21 bp and a third, almost perfect repeat of 22 bp.…”
mentioning
confidence: 99%